Poor Sensorium at the Time of Intubation Predicts Polymicrobial Ventilator Associated Pneumonia - Natarajan R; Ramanathan V; Sistla S (Dove Medical Press, 2022)
Ramachandran Natarajan,1 Venkateswaran Ramanathan,1 Sujatha Sistla2 1Department of Medicine, Jawaharlal Institute of Postgraduate Medical Education and Research, Puducherry, India; 2Department of Microbiology, Jawaharlal Institute of Postgraduate Medical Education and Research, Puducherry, IndiaCorrespondence: Venkateswaran Ramanathan, Department of Medicine, Jawaharlal Institute of Postgraduate Medical Education and Research, Dhanvantri Nagar, Puducherry, 605006, India, Email drvenks@gmail.comBackground: Ventilator-associated pneumonia (VAP) is the most common nosocomial infection in the intensive care unit and is associated with a high mortality rate.Aim: The study was conducted to estimate the frequency, outcomes, and predictors of polymicrobial VAP.Methods: A prospective observational study was conducted in mechanically ventilated adult patients in the medical intensive care unit in a tertiary care hospital in India from July 2016 to July 2018 with a 30-day follow-up period. The patients were grouped into monomicrobial and polymicrobial VAP. We compared the 30-day outcome parameters such as discharge from hospital, in-hospital stay, death, and complications such as catheter associated urinary tract infection (CAUTI), central line associated blood stream infection (CRBSI), bacteremia and collapse of lung. The predictors of polymicrobial VAP were identified by multiple logistic regression.Results: Out of 301 patients clinically diagnosed with VAP, 151 patients were excluded, and the remaining 150 developed 186 episodes of VAP during the study period. The incidence of polymicrobial VAP was 62.9%. Out of 150 patients, 51 patients had monomicrobial VAP, and 99 had polymicrobial VAP. On univariate analysis, diabetes mellitus and poor sensorium (Glasgow Coma Scale [GCS] score < 8) during endotracheal intubation; 30-day outcome, mean days of mechanical ventilation after VAP diagnosis and days in ICU; and CAUTI were significantly associated with polymicrobial VAP. On multivariable logistic regression, poor sensorium (GCS score < 8) at the time of endotracheal intubation was an independent predictor of polymicrobial VAP.Conclusion: The incidence of polymicrobial VAP is high in the medical ICU and is associated with increased duration of mechanical ventilation, hospital stay, and incidence of CAUTI. Poor GCS score was the single independent predictor of polymicrobial VAP.Keywords: monomicrobial VAP, nosocomial infection